Antisense oligonucleotides: a novel Frontier in pharmacological strategy - Collotta, D.; Bertocchi, I.; Chiapello, E.; Collino, M. (Frontiers in Pharmacology, 2023)
Antisense oligonucleotides (ASOs) are short single stranded synthetic RNA or DNA molecules, whereas double-stranded RNA nucleotide sequences are called small interfering RNA (siRNA). ASOs bind to complementary nucleic acid sequences impacting the associated functions of the targeted nucleic acids. They represent an emerging class of drugs that, through a revolutionary mechanism of action, aim to directly regulate disease-causing genes and their variants, providing an alternative tool to traditional "protein-specific" therapies. The majority of the ASOs are designed to treat orphan genetic disorders that in most of the cases are seriously disabling and still lacking an adequate therapy. In order to translate ASOs into clinical success, constant technological advances have been instrumental in overcoming several pharmacological, toxicological and formulation limitations. Accordingly, chemical structures have been recently implemented and new bio-conjugation and nanocarriers formulation strategies explored. The aim of this work is to offer an overview of the antisense technology with a comparative analysis of the oligonucleotides approved by the Food and Drug Administration (FDA) and the European Medicines Agency (EMA).